2023
DOI: 10.3390/cimb45010027
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Highbush Blueberry (Vaccinium corymbosum L.) Anthocyanin Biosynthesis Related MYBs and Functional Analysis of VcMYB Gene

Abstract: As one of the most important transcription factors regulating plant anthocyanin biosynthesis, MYB has attracted great attentions. In this study, we identified fifteen candidate anthocyanin biosynthesis related MYB (ABRM) proteins, including twelve R2R3-MYBs and three 1R-MYBs, from highbush blueberry. The subcellular localization prediction results showed that, with the exception of VcRVE8 (localized in chloroplast and nucleus), all of the blueberry ABRMs were nucleus-localized. The gene structure analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Healthy and uniform blueberry leaves without mechanical injuries were submerged in A. tumefaciens inoculation solution, vacuumed for 20 min, cultured in the dark for 1 d and moved to normal light condition for five days. Then, total flavonoid and anthocyanin content in blueberry leaves was determined according to Fu et al [ 51 ] and Zhang et al [ 20 ], respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthy and uniform blueberry leaves without mechanical injuries were submerged in A. tumefaciens inoculation solution, vacuumed for 20 min, cultured in the dark for 1 d and moved to normal light condition for five days. Then, total flavonoid and anthocyanin content in blueberry leaves was determined according to Fu et al [ 51 ] and Zhang et al [ 20 ], respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Blueberry ( Vaccinium corymbosum L.) is a perennial shrub belonging to the genus Vaccinium of the family Ericaceae. Its fruits are rich with anthocyanins and it is one of the most ideal materials for anthocyanin metabolism research [ 19 , 20 , 21 ]. Plant CHSs usually had multi-gene family characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the absence of ANR promotes anthocyanin synthesis and increases anthocyanin content in Arabidopsis [24,25]. The ANR gene has been identified in tea tree [26][27][28], blueberry [29], apple [30], grape [31][32][33], peach [34], mango [35], and safflower [36], among other plants. In the study on the postharvest physiology of lychee, laccase was found to play a catalytic role in pericarp browning [37].…”
Section: Introductionmentioning
confidence: 99%
“…Considering postharvest qualities, candidate genes of plum associated with pulp color, anthocyanin biosynthesis and flavonoid biosynthesis [ 8 ], anthocyanin biosynthesis related MYBs in highbush blueberry [ 9 ], the potential genetic loci controlling quality traits of melons [ 10 ], and genes responsible for softening and ripening in kiwifruit cultivars treated with ethylene [ 11 ] were reported.…”
mentioning
confidence: 99%
“…Generally, as this special issue belongs to the section “Molecular Plant Sciences” and considering the interest of authors to contribute in this special issue, the editorial team tried to observe the broad spectrum, and eleven research articles [ 2 , 3 , 4 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ] and two reviews [ 1 , 5 ] were included.…”
mentioning
confidence: 99%